2008
DOI: 10.1097/hjr.0b013e32830edc32
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of hypertension in a semiurban community in Nigeria

Abstract: The prevalence estimates of hypertension obtained in this study was higher than those found in most earlier studies from Nigeria, other West Africa nations and for African-Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
79
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 27 publications
15
79
6
Order By: Relevance
“…Female diabetes patients tended to be older than male patients with the difference in mean age attaining statistical significance in 3 out of the 31 years under review. The rising rates of diabetes admissions and increasing mean age of admitted patients is reflective of the increasing longevity of the citizenry of Ghanaians most especially females [23,29,30]. The 28-day in-patient mortality from diabetes admissions of 18.5% observed in this study ranks among the highest in the published literature.…”
Section: Discussionsupporting
confidence: 50%
“…Female diabetes patients tended to be older than male patients with the difference in mean age attaining statistical significance in 3 out of the 31 years under review. The rising rates of diabetes admissions and increasing mean age of admitted patients is reflective of the increasing longevity of the citizenry of Ghanaians most especially females [23,29,30]. The 28-day in-patient mortality from diabetes admissions of 18.5% observed in this study ranks among the highest in the published literature.…”
Section: Discussionsupporting
confidence: 50%
“…Figure 1 is a summary of the selection process. These cross-sectional studies were published between 1960 and 2012 in 12 of the 36 states of Nigeria: Oyo [9][10][11][12][13][14][15][16][17][18][19][20][21][22] , Enugu [23][24][25][26][27] , Lagos [28,29] , Osun [30,31] , Edo [32][33][34][35] , Cross-River [36,37] , Akwa-Ibom [37] , Rivers [38] , Kastina [39] , Sokoto [40] , Borno [41] and Abia [42] . Three of the studies involved more than one state [37,43] .…”
Section: Resultsmentioning
confidence: 99%
“…For 1990-1999 Impact of blood pressure cut-off threshold on the prevalence of hypertension: In a study of the prevalence and patterns of hypertension in a semi-urban community in South Western Nigeria, Adedoyin et al [31] demonstrated that with a cut-off value of ≥ 140/90 mmHg for the diagnosis of hypertension, the prevalence was 36.6% (isolated systolic hypertension (ISH) in 22.1% and isolated diastolic hypertension (IDH) in 14.5%).…”
Section: Pooled Prevalence and Trendmentioning
confidence: 99%
“…29 In Accra and Ashanti regions of Ghana, 28.3 and 29% of the population, respectively have hypertension. 17,30 Data from the National Health and Nutritional Examination Surveys showed that 28 and 29% of United States adults aged 18 or more years have prehypertension and hypertension, respectively.…”
Section: Discussionmentioning
confidence: 99%